Isolation and characterization of antibiotic-resistant bacteria from pharmaceutical industrial wastewaters. (December 2015) - Tahrani, Leyla; Soufi, Leila; Mehri, Ines; Najjari, Afef; Hassan, Abdenaceur; Van Loco, Joris; Reyns, Tim; Cherif, Ameur; Mansour, Hedi Ben
Abstract: Contamination of surface waters in underdeveloped countries is a great concern. Treated and untreated wastewaters have been discharged into rivers and streams, leading to possible waterborne infection outbreaks which may represent a significant dissemination mechanism of antibiotic resistance genes among pathogenic bacterial populations. The present study aims to determine the multi-drug resistance patterns among isolated and identified bacterial strains in a pharmaceutical wastewater effluent in north Tunisia. Fourteen isolates were obtained and seven of them were identified. These isolates belong to different genera namely, Pseudomonas, Acinetobacter, Exiguobacterium, Delftia and Morganella . Susceptibility patterns of these isolates were studied toward commonly used antibiotics in Tunisia. All the identified isolates were found to have 100% susceptibility against colistin sulfate and 100% resistance against amoxicillin. Among the 11 antibiotics tested, six patterns of multi-drug resistance were obtained. The potential of the examined wastewater effluent in spreading multi-drug resistance and the associated public health implications are discussed. Highlights: Significant dissemination mechanism of antibiotic resistance genes. Multi-drug resistance patterns among isolated and identified bacterial strains. Multiresistant bacteria in the public health deterioration.